Performance indicators for the road police public service: bibliometric and systemic analysis - Gomes, Washington Antonio Oliveira; Carvalho, Raphaela Martins de; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
Performance indicators include management tools used to measure the performance of one or more activities from data records. For public management, these indicators can demonstrate whether management is being effective or not, and in this way, contribute to the direction of decision makers in relation to achieving the desired objectives. In the context of public safety on highways, the identification of improvements in this service becomes essential, given its importance for combating various forms of crime, as well as preventing accidents. Thus, this article aimed to carry out a quantitative and qualitative analysis of the researches that explore the performance indicators for the public road police service, from 1995 to 2018. For that, a search was made in the Web of Science database with keywords, and then bibliometric and systemic analyzes were performed. As a result, 56 articles were obtained from the general search and, after applying filters, aiming at selecting only studies directly related to the theme "Performance indicators for the road police public service", a single scientific article was found. The object stipulated by the research is of extreme social relevance, since it addresses works related to public safety on highways, an essential activity for the reduction of national violence and mortality. However, the gap for this field of knowledge is evident, given the scarcity of search, which portrays the need for incentives in studies in this area, enabling improvements in these services, and consequently, in social well-being.
Keywords: Public service; indicators; police; road; public security